EMOTIONAL ANALYSIS OF GO MOON YOUNG CHARACTERS IN THE DRAMA “IT'S OK TO NOT BE OKE” - Nur Intan Permatasari; Delfina Fatihayah; Dyah Kristyowati; Ira Resmayasari (The Journal Of English Teaching For Young And Adult Learners, 2022)
This study aims to determine the emotional character of Go Moon Young, who is the main character in thedrama "It's okay to not be okay". This drama tells about a person named Go Moon Young, a character whohas an antisocial personality disorder and has a dark past that makes Go Moon Young have a bad temperand don't care about other people. Abandoned by his parents when he was young, Go Moon Young livedalone into adulthood and managed to become a famous children's story book writer. In this study,qualitative methods were used, statistical methods and other calculations did not give results, and theresearcher tried to understand the meaning of the events of the interaction of human behavior in certainsituations, and interpret your point of view. The result is a very emotional influence on the socialenvironment such as being shunned by the surrounding community, less sensitive to others, hurtingyourself and always feeling lonely.